Evaluación potencial maderable del bosque local Mahuizo, distrito de Sarayacu, provincia de Ucayali, región Loreto, Perú - Noriega Caballero, Raul Alberto (2013)
This thesis work was carried out with the annual operating plan 01 (Poa 01) of the local forest "mahuiso", which is located in the district of Sarayacu, Province of Ucayali, Region Loreto. Peru. The area of the local forest is 500 ha, the specific area of the study was 124.9 ha. The proposed objectives were to identify the floristic composition of commercial species; determine the Importance Value Index (IVI) of the species of the forest under study; define the possible uses of registered commercial species; and present proposed guidelines for the management plan. For the 100 % forest inventory, the Systematic Strip Design was used, with 20 sampling units of 50 m wide x 12,000 m long; For the collection of field data in the forest inventory, commercial trees ? 40 cm DBH in each sampling unit were considered. The results indicate that 04 commercial species have been registered in 04 botanical families, the most representative being Capirona decorticans "capirona". The potential use of the identified species is: they are sawmill, construction, fuel, parquet, tablets, medicinal, crafts.